Bridging the gaps: An integrated approach to assessing aid effectiveness - Heiner Janus; Paul Marschall; Hannes Öhler (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
Does aid contribute to development? If so, under what conditions and to what extent? These questions are as old as the field of development policy itself and they have been controversially discussed among researchers and policymakers ever since. Yet, two main trends put questions related to aid effectiveness high on the political agenda again. First, development actors want to understand and improve their contribution to the Sustainable Development Goals (SDGs). Second, populist parties on the radical right fundamentally question the relevance of aid and thereby bring development policy to the fore of public debates in donor countries. In response, donors feel more pressure to demonstrate and communicate the success of aid. Since the early 2000s, donors' efforts to meet their commitments under the international aid and development effectiveness agenda have contributed to a plethora of knowledge on what works, what doesn't work, and why. In parallel, academics have contributed new insights through the study of, for instance, macro effects, impact measurements and research on donor organisations. Increasingly, though, the debate on aid effectiveness has become compartmentalised and fragmented. This briefing maps these fragmented discussions and proposes an integrated approach to aid effectiveness in research and policymaking. We argue that only an integrated perspective can match the new demands for why, when and how aid can make a difference. Typically, policymakers and researchers operate in one or more of four (often disconnected) communities, working on: 1) macro effects of aid; 2) global principles for development cooperation; 3) the structure and instruments of organisations; 4) the impact of individual interventions. The first community focuses on research comparing the effects of aid across countries, especially regarding the effect of aid on economic growth or other development indicators. Recently, this analysis has extended to subnational levels and development actors who do not report development finance as per Official Development Assistance (ODA) guidelines, such as China. The second community engages in the promotion of global principles of effectiveness agreed on by 'traditional' providers of aid and partner countries. Five principles of aid effectiveness were enshrined in the 2005 Paris Agenda. As a follow-up, the Global Partnership for Effective Development Cooperation (GPEDC) was created in 2011. The third community is concerned with managing development organisations. Development organisations have increasingly applied results-based management tools to steering operations, accountability, learning and communicating. The fourth community focuses on development interventions and the effectiveness of specific development projects. There has been a shift towards more rigorous methods for evaluating project impacts and efforts to aggregate evidence through systematic reviews. The key insight from our analysis is that an integrated approach to assessing aid effectiveness across the four communities can help to leverage synergies and avoid unintended consequences. For instance, it can improve coordination within development organisations and foster joint knowledge creation among researchers. Finally, an integrated perspective can help to clarify the contribution made by aid to the SDGs vis-à-vis that of other policy fields, and can assist in better communicating the effects of aid to the public.
Keywords: 330; Sustainable Development Goals; Paris Declaration on Aid Effectiveness